Changes in metabolic syndrome status and risk of chronic kidney disease over a decade of follow-up in the Iranian population - Maryam Kabootari; Reza Habibi Tirtashi; Atefeh Amouzegar; Safdar Masoumi; Fereidoun Azizi; Atieh Amouzegar (Scientific Reports)
Abstract This study assessed the effect of MetS status changes over 3 years on the long-term risk of CKD. The analysis included 5686 participants aged ≥ 20 years without pre-existing CKD (57.5% women), followed for a median of 15 years. Participants were classified into 4 groups according to their baseline MetS status and its changes: stable MetS-free, MetS-developed, MetS-recovered, and stable MetS. Hazard ratios (HR) of incident CKD with a 95% confidence interval (CI) were calculated using Cox’s proportional hazard models, adjusted for age, sex, education, physical activity, smoking status, and MetS components. During follow-up, a total of 1360 CKD (women = 881) occurred. Compared to the stable MetS-free group, the stable MetS [HR 1.34 (95% CI 1.06–1.71)] and MetS-developed [HR 1.22 (95% CI 1.03–1.45)] groups had a higher CKD risk. Conversely, recovery from MetS was not significantly associated with CKD risk. However, when using the stable MetS group as the reference, recovery from MetS was linked to a significant 23% lower CKD risk. Considering MetS component changes, persistent elevated blood pressure, elevated blood glucose, and high triglyceride, as well as recovered central obesity and new-onset high triglyceride, significantly impacted CKD incidence. In conclusion, persistent or newly developed MetS increased CKD risk, whereas recovery from MetS reduced the risk compared to persistent MetS.